2017
DOI: 10.1007/s12274-017-1568-5
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of interface on mid-infrared photothermal response of MoS2 thin film grown by pulsed laser deposition

Abstract: Here we report mid infrared (mid-IR) photothermal response of multi layer MoS2 thin film grown on crystalline (p-type silicon and c-axis oriented single crystal sapphire) and amorphous substrates (Si/SiO2 and Si/SiN) by pulsed laser deposition (PLD) technique. The photothermal response of the MoS2 films was measured as changes in the resistance of MoS2 films when irradiated with mid IR (7 to 8.2 μm) source. We show that it is possible to enhance the temperature coefficient of resistance (TCR) of the MoS2 thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
1
20
1
Order By: Relevance
“…Similar broadband absorption in the NIR and MIR regions was obtained by Goswami and et al for the bulk MoS 2 films. 24 As expected, the absorption of the films increased with the film thickness. Owing to this strong absorption of the films in these regions, it is considered that they can be used for IR detection applications.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Similar broadband absorption in the NIR and MIR regions was obtained by Goswami and et al for the bulk MoS 2 films. 24 As expected, the absorption of the films increased with the film thickness. Owing to this strong absorption of the films in these regions, it is considered that they can be used for IR detection applications.…”
Section: Resultssupporting
confidence: 72%
“…15 These properties make MoS 2 a promising material in future nanoscale electronic and optoelectronic device applications such as photocatalysis, 16 photodetectors, 17 biosensors, 18 gas sensors, 19 phototransistors, 20 field-effect transistors (FETs), 21 solar cells 22 and light-emitting diodes (LEDs). 23 There have been many various attempts including top-down and bottom-up methods such as mechanical exfoliation, 24 chemical exfoliation, 25 hydrothermal synthesis, 26 physical vapor deposition (PVD), 27 and chemical vapor deposition (CVD) 28 to produce MoS 2 thin films. Initially, researchers have intensely focused on the exfoliation method for obtaining monolayers of MoS 2 films and it is still the most commonly used method for the growth of MoS 2 films.…”
Section: Introductionmentioning
confidence: 99%
“…2H MoS 2 multi-layers were grown through pulsed mid-infrared laser deposition [147] (wavelength of 7.0-8.2 µm). No any IR damage was reported.…”
Section: Infrared Light Irradiationmentioning
confidence: 99%
“…Goswami et al demonstrated a TCR up to −2.9% K −1 at room temperature in pulsed laser deposition (PLD)–grown MoS 2 film on silicon substrate. Their reported MoS 2 bolometers were sensitive to mid‐IR irradiation (7–8.2 µm) with a responsivity of 8.7 V W −1 and response time on the order of 10 s . Superconductors are also known to show a very strong resistance dependence on temperature near the critical temperature T c , and have been proposed as sensitive superconducting bolometers .…”
Section: D‐based Photodetectorsmentioning
confidence: 99%